Stability Control Mechanism of High-Stress Roadway Surrounding Rock by Roof Fracturing and Rock Mass Filling - Fuzhou Qi; Zhanguo Ma; Dangwei Yang; Ning Li; Bin Li; Zhiliu Wang; Weixia Ma (Advances in Civil Engineering)
Large deformation of roadway and coal bump failures have always been the focus in deep underground engineering. By considering the Lu’an mining district in China, the failure mode and stability improvement process of high-stress roadways were analysed with the field tests and numerical simulations. The field test results showed that a great amount of deformation and serious damage occurred in surrounding rocks during panel retreat due to the suspended roof. A novel approach employing roof fracturing and collapsed rock filling effect was adopted to maintain the roadway stability. A numerical model was established with the Universal Distinct Element Code (UDEC) to research the fracturing characteristics between the roadway and gob roofs and the stress change in the surrounding rock. The modelling results demonstrated that, without fracturing roof, the peak vertical stress of the coal pillar was 18.3 MPa and the peak vertical stress of the virgin coal rib was 15.6 MPa. The roadway was in a state of high stress. With fracturing roof, the peak vertical stress of coal pillar was 9.3 MPa and the peak vertical stress of virgin coal rib was 13.4 MPa. The fractured rock mass in the gob expanded in volume and provided supporting resistance to the overlying strata, which relieved stress concentrations in the coal pillar. Field measurement results indicated that the roadway large deformation was successfully resolved during excavation and panel retreat after implementing the novel approach, providing useful references for the application of this novel approach in similar coal mines.